Pendidikan Karakter Dalam Pembentukkan Akhlak Mulia Di MTS ISTIQLAL DELITUA - Sarah Audry Lubis; Zuliana (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
This PKP activity is one of the subjects that must be taken for students who take the level or degree of an undergraduate education study program. This PKP activity was carried out covering several stages, namely the preparation stage and the implementation stage, starting from observation, learning, consultation, teacher guidance, and preparation of learning tools including: lesson plans, syllabus, modules, teacher workbooks, and learning media. At this time the author was entrusted with the responsibility of teaching the material "Islamic Education" which was held on September 2 and ended on September 24, in carrying out the activities of holding one meeting with a minimum of 8 meetings in a predetermined time. A lot of experience is gained on how to become a teacher who has good competence. The real experience gained in learning and acting is one of the most valuable experiences. As a teacher, it is necessary to prepare in teaching and managing the class to be more effective.